2021
DOI: 10.1016/j.arth.2020.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Hyaluronic Acid Injections Less Than 6 Months Before Total Hip Arthroplasty: Is It Safe? A Retrospective Cohort Study in 565 Patients

Abstract: Background: Intra-articular hyaluronic acid (IAHA) can be injected into an osteoarthritic hip joint to reduce pain and to improve functionality. Several studies report IAHA to be safe, with minor adverse effects that normally disappear spontaneously within a week. However, intra-articular corticosteroids prior to total hip arthroplasty (THA) have been associated with increased infection rates. This association has never been investigated for IAHA and THA. We aimed to assess the influence of IAHA on the outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Our study cohorts may have included those with undeclared confounding interventions with potential to influence PJI. These modalities may have included intraarticular synovial fluid supplementation [45], intraarticular injectable cellular therapies (such as PRP or BMAC) [46] and potentially acupuncture [47]. Additionally, the number of ICSI provided in the study period was unclear in most studies.…”
Section: Table III Risk Of Bias Analysis Using the National Institute...mentioning
confidence: 99%
“…Our study cohorts may have included those with undeclared confounding interventions with potential to influence PJI. These modalities may have included intraarticular synovial fluid supplementation [45], intraarticular injectable cellular therapies (such as PRP or BMAC) [46] and potentially acupuncture [47]. Additionally, the number of ICSI provided in the study period was unclear in most studies.…”
Section: Table III Risk Of Bias Analysis Using the National Institute...mentioning
confidence: 99%
“…Seven studies were excluded with reasons. Finally, 19 studies were included in this systematic review and meta-analysis (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Search and Study Detailsmentioning
confidence: 99%
“…Multiple recent studies have reported that the time interval between the IAI and the THA is an important factor with regard to the risk of infection. [29][30][31]35,38,40 However, the literature does not agree on a definitive time window after IAI when it is safe to proceed to THA.…”
Section: Newer Evidencementioning
confidence: 99%